ANALISIS DESAIN BANGUNAN PENGAMAN PANTAI (SEAWALL) DI KECAMATAN BINAMU KABUPATEN JENEPONTO - Said, Sugira (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2024)
One of the districts in South Sulawesi Province which has a coastal area is Jeneponto Regency. For the people of Jeneponto, this coastal area is important not only because of its rich diversity but also because of its economic activities, including fishing, seaweed cultivation and recreation. However, currently coastal erosion in Jeneponto Regency is very serious. Natural systems will deteriorate if prevention of sea water erosion is not implemented, altering coastlines in the process. The aim of this research is to evaluate the design of beach safety buildings that will be used at Tamarunang Beach and look for alternative countermeasures that will be built. The analysis process involves selecting replacement coastal protection structures and design calculations. Sea walls or hexagonal concrete supports are the treatment with the most points according to the matrix used in this research to select alternative coastal safety construction. However, when choosing beach treatment, you need to consider the various conditions along Tamarunang beach. In terms of community willingness, as long as security measures do not hinder the flow of boats carrying fishermen and seaweed farmers, then the community may be given protection along the Tamarunang coast. Based on the research results, the following conclusions can be drawn: 1. The height of the sea wall is 2.44 meters; 2. The stone used for the sea wall weighs 27 kg; and 3. The diameter of the stone is 27 cm.